STRATEGI PENGEMBANGAN GEOPARK MERANGIN JAMBI SEBAGAI TAMAN BUMI DUNIA (UNESCO GLOBAL GEOPARK): Akselerasi Pengembangan dan Optimalisasi Pengelolaan Geopark Merangin - Abdul Rahman; Murtir Jeddawi; Umar (Post Graduate School of Government Science, 2025)
The development of Merangin Geopark in Jambi as a prospective UNESCO Global Geopark faces complex challenges, including limited infrastructure, low accessibility, inadequate tourism amenities, and suboptimal community participation. Analyzing the current governance of the management and development of Merangin Jambi Geopark, viewed from the perspective of community-based tourism, community empowerment, stakeholder synergy (government, business actors, and local communities), and the implementation of tourism branding; and examining the most relevant and sustainable development strategies to strengthen the governance of Merangin Jambi Geopark in order to meet the criteria of a UNESCO Global Geopark. Using a qualitative descriptive approach, data were collected through in-depth interviews, observations, and document analysis involving government officials, local communities, and tourism actors. The results show that while the Merangin Regional Government has integrated geopark development into its official planning documents (RPJMD, RIPP, and Master Plan), the implementation remains fragmented and lacks coordination among stakeholders. Community empowerment and tourism branding efforts have been initiated but have yet to generate substantial impact due to limited participation and promotional activities. The study concludes that an effective strategy for Merangin Geopark development requires accelerating policy implementation, strengthening community-based tourism, fostering public–private partnerships, and creating a distinctive tourism brand that reflects local geological and cultural uniqueness. These integrated efforts are essential to position Merangin Geopark as a sustainable world-class geotourism destination.